A Comparative Analysis of Critical Thinking in Western And Islamic Education: Implications for Contemporary Islamic Pedagogy - Rabiatul Adawiah; Halimatus Sakdiah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
Critical thinking is an important skill in education, but its conceptualization varies across Western and Islamic paradigms. This study aims to compare the concepts, criteria, and objectives of critical thinking in Western and Islamic education. The research method used is a qualitative literature study by examining primary and secondary sources from Western and Islamic studies, and analyzing them systematically thematic. The main findings reveal that Islamic critical thinking